Solution Studies and Biological Activity of Some Bivalent Metal Complexes with Schiff Bases Derived From 3-Phenyl Salicyladehyde - Shetye, S.S.; Mayadeo, (Late); Laxmeshwar, N.B. (Asian Journal of Chemistry, 2010)
Potentiometric studies have been carried out on metal complexes of Cu2+, Ni2+, Co2+, Zn2+, Cd2+ and Mg2+ with N-[3-phenyl salicylidine]-4-methoxy aniline, N-[3-phenyl salicylidene]-2,5-dimethoxy aniline, N-[3-phenyl salicylidene]-2,5-dimethoxy-4-nitroaniline. The stability constants of the regents and their bivalent metal ion chelates have been determined by Calvin-Bjerrum pH titration technique as adopted by Irving and Rossotti at 303 K and at an ionic strength of 0.1 Min 75 : 25 (v/v) dioxane-water medium. Since the above reagents investigated by us are good chelating agents they were also screened for their antibacterial and anticoagulant activity.